2005
DOI: 10.1111/j.1744-7429.2005.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Distribution of the Amphibian Pathogen Batrachochytrium dendrobatidis in the New World1

Abstract: One application of ecological niche modeling is predicting suitable areas for the establishment of invasive species. Herein, I model the fundamental niche of the chytrid fungus Batrachochytrium dendrobatidis, a pathogen linked to amphibian declines on several continents. Niche models were generated with the Genetic Algorithm of Rule‐Set Prediction using point distribution data of the pathogen and digital maps of environmental variables integrated in a GIS environment. The distribution of regions suitable for B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
209
5
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(262 citation statements)
references
References 54 publications
28
209
5
20
Order By: Relevance
“…Indeed, bioclimatic modeling predicts that the fungus is more likely to inhabit wetter regions (Ron, 2005), and recent field studies confirm this prediction. Kriger et al (2007) found that both the prevalence and intensity of B. dendrobatidis infections in eastern Australia increase significantly in regions with high rainfall.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Indeed, bioclimatic modeling predicts that the fungus is more likely to inhabit wetter regions (Ron, 2005), and recent field studies confirm this prediction. Kriger et al (2007) found that both the prevalence and intensity of B. dendrobatidis infections in eastern Australia increase significantly in regions with high rainfall.…”
supporting
confidence: 49%
“…One explanation, the climate-linked epidemic hypothesis, has received increased attention in recent years (Pounds and Crump, 1994;Pounds et al, 1999;Kiesecker et al, 2001;Pounds, 2001;Harvell et al, 2002;Ron et al, 2003;Pounds and Puschendorf, 2004;Lampo et al, 2006;Pounds et al, 2006;Santiago-Paredes and La Marca, 2006;Alford et al, 2007;Bosch et al, 2007;Di Rosa et al, 2007;Pounds et al, 2007;Laurance, 2008;Lips et al, 2008). Although it is increasingly clear that various climate anomalies can alter the dynamics of host-pathogen systems (Harvell et al, 2002;Pounds et al, 2007), I suggest caution before accepting the hypothesis that prolonged or intensified dry seasons trigger or exacerbate epidemics of chytridiomycosis, a scenario hypothesized by several authors (Pounds et al, 1999;Ron et al, 2003;Burrowes et al, 2004;Pounds and Puschendorf, 2004;Lampo et al, 2006;Santiago-Paredes and La Marca, 2006), but for which no empirical data exist. To distinguish this hypothesis from other climate-linked epidemic hypotheses, I will hereafter refer to it as the drought-linked chytridiomycosis hypothesis.…”
mentioning
confidence: 99%
“…We collected 27 predictor variables (electronic supplementary material, table S1) from different publications and public databases (see the electronic supplementary material, appendix S2). These predictors can be grouped into seven categories: (i) 19 climatic variables and elevational data at a resolution of 2.5 arc-min [18], (ii) global land use, (iii) introduced hosts variable using all available records of the 28 most widely distributed introduced amphibian host species [25] (see the electronic supplementary material, appendix S3), (iv) global trade and frog leg trade data for each country, (v) the human footprint as an index of biome-type-corrected human influence on the surface of the Earth [28], (vi) the average (1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) normalized difference vegetation index (NDVI) as a vegetation and habit metric, and (vii) amphibian species richness by overlaying GIS historical range maps of 6188 amphibian species from the IUCN Global Amphibian Assessment. All non-climatic variables were resampled to the 2.5 arc-min resolution to match the bioclimatic variables using a bilinear interpolation function, which is considered more realistic than the simpler nearest-neighbour method [31].…”
Section: Materials and Methods (A) Data Collectionmentioning
confidence: 99%
“…Bd is widely considered one of the principal drivers of the global decline of amphibians [13], the most threatened vertebrate taxon on the Earth [14]. There have been several SDMs for Bd that use environmental predictors to explain Bd occurrence patterns [15][16][17][18]. Although these studies are useful for predicting Bd risk and making relevant management strategies, they mostly focus on FN predictors, or only limited PP factors, such as human population density at a continental scale [15].…”
Section: Introductionmentioning
confidence: 99%
“…For chytridiomycosis, bioclimatic models have an important role to play in identifying currently uninfected areas into which the disease could be expected to spread [66]. On a global level, these include Madagascar, Borneo and New Guinea [85]. Concerningly for the latter two, the fungus has recently been isolated from Indonesia [86].…”
Section: (A) Isolating Infected Populationsmentioning
confidence: 99%